RAJUTAN SEMIOTIKA UNTUK SEBUAH IKLAN STUDI KASUS IKLAN LONG BEACH - H. Istanto, Freddy (Institute of Research and Community Outreach - Petra Christian University, 2000)
Semiotics is the study of signs and symbols. The theory of which originated from the Language Theory. It is reliable as an analysis method in examining signs. The products designed and created instinctively could be scientifically reasoned by Semiotics. In this study case on cigarette ads of Long Beach pizza-man version%2C the semiotics approach is used. Using the Semiotics theory%2C the analysis between the signifier and the signified in the implementation of the ad accentuates the study. Abstract in Bahasa Indonesia : Semiotika adalah ilmu tentang tanda. Semiotika adalah sebuah teori yang berasal dari teori bahasa%2C namun memiliki keandalan sebagai metoda analisis untuk mengkaji tanda. Semiotika juga mengantar produk-produk rancangan terakomodasi untuk diilmiahkan. Lewat studi kasus iklan rokok Long Beach versi Pizza-man%2C pendekatan semiotika digunakan untuk membedah iklan rokok ini. Kupasan antara penanda (signifier) dan petanda (signified) dalam eksekusi iklan ini memperjelas kajian kasus dengan teori semiotika. semiotics%2C semiotics-theory%2C Long Beach.